تفاعالت صبغة بنفسج البمور مع عزالت سريريه من بكتريا المكورات العنقودية الذهبية - ناصر, محمد لفته عطا الله (Al-Nahrain Journal of Science, 2018)
One hundred isolates of Staphylococcus aureus were cultivated on crystal violet agar. fifty isolates were isolated from superficials sites and the other fifty isolates were isolated from wounds sites. one isolate from superficials isolates gave purple reaction with crystal violet stain. While the all remain isolates gave white reaction.